Hydroxyphenyl Butanone Induces Cell Cycle Arrest through Inhibition of GSK3β in Colorectal Cancer. (3rd July 2021) - Zhang, Songyan; Wang, Yunfeng; Zhang, Haopeng; Sun, Chengming; Dang, Shuwei; Liu, Ming
Abstract : Background . Colorectal cancer (CRC) is among the top three gastrointestinal malignancy in morbidity and mortality. The abnormal activation of Wnt/ β -catenin pathway is considered to be a key factor in the occurrence and development of CRC. Novel inhibitor discovery against key factor in WNT pathway is important for CRC treatment and prevention. Methods . Cell proliferation was detected after hydroxyphenyl butanone treatment in human colorectal cancer HCT116, LOVO, and normal colonic epithelial NCM460 cells. Colony formation, cell invasion ability, and cell cycle were detected with and without GSK-3 β knockdown. Results . Hydroxyphenyl butanone induces cycle arresting on G1-S phase of colorectal cancer cell line through GSK3 β in Wnt/ β -catenin pathway and inhibits malignant biological manifestations of cell proliferation, colony formation, and invasion. The inhibition in the high concentration group is stronger than that in the low concentration group, and the antitumor effect is different for different tumor cells. Under the same concentration of natural hydroxyphenyl butanone, the inhibition on normal colonic epithelial cells is significantly lower than that on tumor cells. The natural hydroxyphenyl butanone with medium and low concentration could promote the proliferation of normal colonic epithelial cells. Conclusion . This study illustrated natural hydroxyphenyl butanone as new inhibitor of GSK3 β and revealed the mechanisms underlying the inhibitory effects in colorectal cancer.